Psychoeducation for Happy Teachers and Joyful Classrooms: Emotional Regulation Skills in Managing the Dynamics of Early Childhood - Lina Rahmawati; Shinta Pratiwi; Mulya Virgonita I.W (Yayasan Meira Visi Persada, 2026)
Teachers' emotional regulation is a critical aspect of early childhood education, yet teachers frequently experience job stress due to misconceptions regarding children's tantrum behaviors. This community service (PKM) program aimed to enhance Kindergarten teachers' emotional regulation capacity through neuroscience-based psychoeducation. The program's partners were Kindergarten teachers who reported stress vulnerability and reactive tendencies when dealing with tantrums. The intervention method involved interactive psychoeducation integrating brain development concepts, specifically the roles of the Amygdala and the Prefrontal Cortex (PFC), followed by qualitative reflective evaluation sessions. The evaluation results indicated a significant cognitive reframing among teachers. Prior to the intervention, teachers attributed tantrums to children's misbehavior, which triggered negative emotional responses. Post-intervention, teachers perceived tantrums as an expression of the biological limitations of a developing child. This paradigm shift reduced emotional tension, enhanced empathy, and increased teachers' self-efficacy in managing classroom dynamics. Neuroscience-based psychoeducation is proven effective in providing long-term impacts on teachers' psychological well-being and the quality of caregiving in schools.